BANDRONG SILAT BASIC STRUCTURE AT PADEPOKAN TUNAS MUDA BOJONEGARA SERANG BANTEN REGENCY - Andri Firmansyah; triena permanasari (Universitas Pendidikan Indonesia, 2022)
Bandrong Silat is a traditional art that was born and developed in the Bojonegara area, Serang, Banten. This research is motivated by the absence of written references regarding the basic movement structure of Bandrong Silat in Padepokan Tunas Muda. This study aims to describe the basic movement structure of Bandrong Silat in Padepokan Tunas Muda. The research method used is descriptive qualitative with an ethnographic approach, because what is analyzed is facts in the field according to local culture. The object of this research is Padepokan Silat Bandrong Tunas Muda Bojonegara, Serang Regency, Banten. The data used comes from the results of observations, interviews and documentation. Based on the results of research on the basic movement structure of Bandrong Silat in Padepokan Tunas Muda, the basic movement called move 1 is divided into 3 parts of motion, namely opening motion, core move, and closing motion. The basic movement grouping includes the hands, including punches, pairs and defenses. The legs are kicks, stances, pairs and defenses. As well as body parts consisting of avoidance, pairs of attitudes, and defense.